Studi Analisa Koordinasi Menggunakan Relay OCR (OVER CURRENT RELAY) Untuk Gangguan Hubung Singkat Pada Penyulang 2 Distribusi 20 KV GI Jajar Surakarta Menggunakan ETAP 12.6 - Sofa, Muhammad Dhoi Fathoni; , Umar, S.T., M.T (2017)
Networks distributed on each feeder have different defects, this is due to several factors: internal and external factors. Efforts to minimize all the disturbance PLN has done maintenance and maintenance. This disorder is caused by the increase of power from the consumer and the power supply flow from the unfavorable distribution, therefore many protection systems are damaged and need more improvement. Installation of protection systems especially on releases becomes an important aspect for the performance of other components, because the protection system becomes the point where the frequent trouble, and although the value of the setting is appropriate but the current surge is still happening. The result of this research is the setting value of PLN for TMS: 0.25 seconds and the setting value of manual calculation performed by TMS author is: 0.18 seconds. There is a difference in value from all the research done, but this as a reference and references for authors for better in the future. The existing system of distribution in feeders 12 is still relatively safe and the setting is still in accordance with the standard of IEEE 242-2986. Keywords: Coordination, Feeder, Short Circuit.